A complex mosaic of enteroviruses shapes community-acquired hand, foot and mouth disease transmission and evolution within a single hospital. Issue 2 (13th July 2018) - Cobbin, Joanna C A; Britton, Philip N; Burrell, Rebecca; Thosar, Deepali; Selvakumar, Kierrtana; Eden, John-Sebastian; Jones, Cheryl A; Holmes, Edward C
Abstract: Human enteroviruses (EV) pose a major risk to public health. This is especially so in the Asia-Pacific region where increasing numbers of hand, foot and mouth disease (HFMD) cases and large outbreaks of severe neurological disease associated with EV-A71 have occurred. Despite their importance, key aspects of the emergence, epidemiology and evolution of EVs remain unclear, and most studies of EV evolution have focused on a limited number of genes. Here, we describe the genomic-scale evolution of EV-A viruses sampled from pediatric patients with mild disease attending a single hospital in western Sydney, Australia, over an 18-month period. This analysis revealed the presence of eight viral serotypes—Coxsackievirus (CV) A2, A4, A5, A6, A8, A10, A16 and EV-A71—with up to four different serotypes circulating in any 1 month. Despite an absence of large-scale outbreaks, high levels of geographical and temporal mixing of serotypes were identified. Phylogenetic analysis revealed that multiple strains of the same serotype were present in the community, and that this diversity was shaped by multiple introductions into the Sydney population, with only a single lineage of CV-A6 exhibiting in situ transmission over the entire study period. Genomic-scale analyses also revealed the presence of novel and historical EV recombinants. Notably, our analysis revealed no association between viral phylogeny, including serotype, and patient age, sex, nor disease severity (for uncomplicated disease). This study emphasizes the contribution of EV-A viruses other than EV-A71 to mild EV disease including HFMD in Australia and highlights the need for greater surveillance of these viruses to improve strategies for outbreak preparedness and vaccine design.